Anthropometric characteristics of four groups of indigenous people of Wallacea in East Indonesia - Rahmawati, Neni Trilusiana; Hastuti, Janatin; Suriyanto, Rusyad Adi (Anthropological Review, 2023)
The human body size varies significantly around the world, both between and within populations. Likewise, ethnic diversity has a significant effect on anthropometric data differences for the Naulu, Tana Ai, Bugis and Rampasasa tribes, in Wallacea, East Indonesia. Six body dimensions were collected from 484 people, 219 males and 265 females in the age from 18 to 80 years. The statistical analysis included tabulating the means and standard deviations for the various body dimensions and proportions. A one-way ANOVA with post hoc LSD test was performed to determine significant differences between the means of anthropometric dimensions and proportions, as well as within the four ethnic groups. There are significant differences (p<0.01) among the four ethnic groups and two sexes in most measurements taken. The post-hoc LSD test indicated that the Naulu male has the largest body size compared to the Tana Ai, Bugis, and Rampasasa tribes. The Naulu have a large body size, a long trunk, broad shoulders, and long legs. Tana Ai and Bugis people have nearly identical characteristics, namely a medium body, long trunk, narrow shoulders and hips, whereas Rampasasa people have a small body size, with a long trunk, narrow shoulders and a wide pelvis. The Naulu and Bugis people have trapezoidal trunks, while the Tana Ai and Rampasasa people have rectangular trunks. In conclusion, the tribes in the Wallace area of East Indonesia have a wide variety of physical characteristics. Further research is needed to understand how changes in technology, development, transportation and large migration flows affect the demographic and physical characteristics of ethnic groups in Indonesia.